Ten-year natural history of visual function in Japanese patients with Leber hereditary optic neuropathy: A retrospective cohort study - Yasuyuki Takai; Akiko Yamagami; Mayumi Iwasa; Kenji Inoue; Ryoma Yasumoto; Hitoshi Ishikawa; Masato Wakakura (PLoS ONE, 2026)
Leber hereditary optic neuropathy (LHON) is a mitochondrial optic neuropathy that typically causes severe bilateral central vision loss. Although several natural-history studies have reported visual outcomes, long-term trajectories beyond 5 years remain incompletely quantified, particularly in Asian cohorts. We performed a single-center retrospective cohort study at a tertiary eye hospital in Japan. Among 174 genetically confirmed LHON patients, we identified 27 patients (53 eyes) who presented within 6 months of onset and were followed continuously for ≥10 years. Best-corrected visual acuity (BCVA, logMAR) was collected from onset to 120 months. Piecewise linear mixed-effects models with patient- and eye-level random effects were fitted over three phases (Acute, < 12 months; Chronic, 12–60 months; Late Chronic, 60–120 months). Kaplan–Meier analyses estimated time to achieving BCVA ≤1.6 and ≤1.3 logMAR. BCVA worsened rapidly after onset, followed by gradual improvement and then an approximately horizontal course. During the Chronic phase, BCVA showed a small but statistically significant improvement (overall −0.030 logMAR/year, 95% confidence interval (CI) −0.045 to −0.015; −0.025 logMAR/year, 95% CI −0.044 to −0.007 in a pre-specified m.11778G > A subgroup). In the Late Chronic phase, estimated slopes were close to zero (+0.003 logMAR/year, 95% CI −0.007 to +0.013 overall), with wide CIs compatible with small long-term improvement or deterioration. By 10 years, the cumulative probabilities of achieving BCVA ≤1.6 and ≤1.3 logMAR were approximately 45% and 26%, respectively. In this Japanese LHON cohort with ≥10 years of continuous follow-up, BCVA showed limited improvement during the early chronic period, and we did not detect a clear directional trend thereafter. Given the modest sample size and selection of long-term attendees, these estimates should be interpreted as descriptive, phase-specific benchmarks rather than definitive evidence of long-term stability or ethnic differences.